Taslima Nasrin’s Criticism of Islam: an Academic Response - Hasan , Md. Mahmudul (2011)
The feminist tradition in what is now Bangladesh took off with Rokeya Sakhawat Hossain (1880-1932) who arguably foregrounds her ideas in Islamic, indigenous culture and exerts a posthumous public influence. However, about one hundred years after Rokeya, Taslima Nasrin (1962-) produced a number of works most critical of Islam, such as Amar Meyebela (1999), Utal Hawa (2002) and Ka (2003), which increased controversy over the content of her feminist work and strategy. Although many Muslims dismiss Taslima’s writings as anti-Islamic provocation and pornography, they are well-received in the West where she is celebrated as a feminist rebel who presumably defies the supposed Bangladeshi Islamic patriarchy. While Rokeya critiques the patriarchal, male-stream interpretation of Islam and reexamines it in light of gender justice, Taslima uncritically takes the prevalent patriarchal notions of Islam as the norm and scapegoats the religion by putting almost the entire blame of gender injustices on it. Based on this observation, my critical analysis of Taslima’s work will examine her overly critical view of Islam and will provide the correct Islamic position with regard to many gender issues Taslima raises in her work. When referring to secondary sources on Islam, she relies hugely on ‘dud’ materials written mainly by semi-educated Muslims and on some spurious hadiths, which this study aims to identify and clarify. This will be a follow-up work to my article titled ‘Free speech, ban and “fatwa”: A study of the Taslima Nasrin affair,’ [Journal of Postcolonial Writing, 46(5) 2010 pp.540-552].